A TEACCH Class Model for Comprehensive Intervention in Children with Autism Spectrum Disorder - Ardianingsih, Febrita; Ashar, Muhammad Nurul; Wijiastuti, Asri (Journal of Education for Sustainability and Diversity, 2023)
Autism Spectrum Disorders (ASD) are pervasive developmental disorders that cover various aspects of development. Interventions using drugs are still not clearly proven to address the core problems of children with autism spectrum disorders, so interventions are directed at non-pharmacological approaches. The aim of this study is to examine the TEACCH class model for comprehensive interventions for children with ASD in all aspects of development. This research uses a qualitative approach. The data sources for this study were a vice principal and two teachers from one of the autism special schools in Malang, East Java, Indonesia. Data collection techniques through interviews and observation. Data analysis used the Miles & Huberman Flow Analysis Model. The validity of the data was carried out by triangulating sources, techniques, and theories. Research findings (1) The minimal TEACCH class model consists of a whiteboard, bench, visual support, and a sensory/quiet corner. Teachers apply TEACCH by implementing structured learning activities (clear, coherent, and predictable activities) and flexible ones (adjusting to the needs of each child) by involving an independent work system. (2) The application of TEACCH can improve the skills of autistic spectrum children in communication, social, emotional-behavior, and cognitive aspects.